Наукові підходи до трактування сутності екологічного менеджменту підприємства - Черчик, Лариса Миколаївна; Cherchyk, Larysa M. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто існуючі підходи до визначення сутності екологічного менеджменту, запропоновано його трактування з позиції інституційного та процесного підходів. Визначено елементи системи екологічного менеджменту та основні етапи процесу екологічного менеджменту підприємства. The article reviews current approaches to defining the essence of environmental management: institutional, process, system and functional; offered his interpretation from the perspective of institutional and process approaches. Under the institutional approach, environmental management company – is a set of principles, forms, methods, techniques and tools of influence that, on the one hand, used enterprise staff to achieve high performance, on the other - providing ecologically activities based on rational and sustainable Nature that does not harm the environment. Defined elements of the environmental management company (subject, object, subject, goal, goals, objectives, instruments, tools, methods, expected results). According to the process approach, environmental management company – a set of interconnected successive stages of management, providing justification, adoption and implementation of management decisions to achieve environmentally sound and cost-effective strategic development of the company, namely: formation of ecology-oriented concept of enterprise development; strategic analysis of the environment; diagnosis ecological and economic security; Forecasting changes in the strategic environment of the company; ecologically goal-setting; study strategic set of enterprise development; development of environmental policy; strategic planning implementation of the chosen strategy; environmental monitoring, audit and control strategies and the implementation of environmental policy; evaluation of the effectiveness of the chosen strategy and environmental policy.
Scientific approaches to the interpretation of the essence of environmental management company
Keywords: підприємство; екологічний менеджмент; екологоорієнтоване стратегічне управління; процес екологічного менеджменту підприємства; enterprise; environmental management; ecologically strategic management; environmental management process of the company